2013
DOI: 10.5539/elt.v6n7p96
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Discourse in Relation to Language Learning in English Classes Co-Taught by Native English-Speaking Teachers and Local Teachers in Taiwan

Abstract: This study attempts to explore the nature and the potential of various discourse structures and linguistic functions that may facilitate students' learning in English classes co-taught by a native English-speaking teacher (NEST) and a local English teacher in Taiwanese elementary schools. Considering the nature of the study, the author employed a case-study approach to investigate the classroom discourse. In the study, data were analyzed based on a theoretical framework combining discourse analysis schemes, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A study by Luo (2013) posited that teacher-reading and student-repeating sessions present a lost opportunity in the classroom for students to develop learner autonomy. Moreover, other research shows limited opportunities for student-initiated participation in the classroom discourse as well as situations that require students' higher-order thinking (Hardman & Abd-Kadir, 2007).…”
Section: Discourse Analysis In Efl Classes: a Teacher's Perspective On Its Benefits And Usesmentioning
confidence: 99%
“…A study by Luo (2013) posited that teacher-reading and student-repeating sessions present a lost opportunity in the classroom for students to develop learner autonomy. Moreover, other research shows limited opportunities for student-initiated participation in the classroom discourse as well as situations that require students' higher-order thinking (Hardman & Abd-Kadir, 2007).…”
Section: Discourse Analysis In Efl Classes: a Teacher's Perspective On Its Benefits And Usesmentioning
confidence: 99%
“…In a study conducted by Luo (2013) the class assumed teacher-reading and student-repeating sessions, presenting a lack of opportunity in the classroom for the students to develop learner autonomy in English learning. Likewise, other classroom research showed limited opportunities for student-initiated participation in the classroom discourse or situations that require students' higher-order thinking cf.…”
Section: • Moreover Research Conducted By Alzobidy and Khan (2019) Revealedmentioning
confidence: 99%
“…Most students did not have the opportunity to use the target language independently and only replied to the teacher in the chorus or repeated what the teacher uttered. That means almost all the classroom activities were teacher-fronted drills (Luo, 2013).…”
Section: • Moreover Research Conducted By Alzobidy and Khan (2019) Revealedmentioning
confidence: 99%
“…These studies dealt predominantly with modes of practice, curricula, teaching materials, and effects of EMI programmes (Lee, 2011;Luo, 2013;Spence & Liu, 2013). Only in the recent past did researchers embark on addressing the testing of teacher performance as part of the evaluation of EMI programmes.…”
Section: Introductionmentioning
confidence: 99%